Eksperimen Pembelajaran Matematika dengan Model Two Stay Two Stray (TS TS) dan Team Assisted Individualization (TAI) Ditinjau dari Motivasi Belajar Siswa SMP Negeri 23 Surakarta Semester Genap - R, Etik Anisa Wulansuci; , Dr. Sumardi, M.Si (2017)
The research aims to analyze and examine: (1) The influence of learning model of Two Stay - Two Stray and Team Assisted Individualization toward mathematics learning outcomes, (2) The influence of learning motivation of student toward mathematics learning outcomes, (3) The interaction between learning model and learning motivation of student towards mathematics learning outcomes. The type of this research is quantitative with quasi experimental design. The population in this research is all students of VIII SMP Negeri 23 Surakarta on academic year 2016/2017. Sample of this research consisted of two classes, they are experiment class and control class with the sampling technique that are use is cluster random sampling. Methods of data collection used tests, questionnaires, and documentation. Techniques of analyzed used analysis of variance two paths with different cell with a significance level of 5%. Results of the data analysis was obtained: (1) There is the influence of learning model of Two Stay - Two Stray and Team Assisted Individualization toward mathematics learning outcomes, (2) There is the influence of learning motivation of student toward mathematics learning outcomes, (3) There is no the interaction between learning model and learning motivation of student towards mathematics learning outcomes. Keywords: : two stay - two stray, team assisted individualization, motivation, mathematics.